Measures of vibrotactile sensitivity in persons exposed to hand-arm vibration. - Hayward, R. A.; Griffin, Michael J. (Scandinavian Journal of Work, Environment & Health, 1986)
A group of 57 persons occupationally exposed to hand-arm vibration was studied in an investigation of factors affecting their vibrotactile thresholds. The group contained 42 persons with symptoms of vibration-induced white finger (VWF). Measures of finger thresholds and temperatures were obtained from both hands. It was found that vibrotactile thresholds were higher in subjects reporting VWF. A laboratory investigation indicated that finger temperature had a great effect on the thresholds but that this effect only occurred outside the range of temperatures found in the study of occupationally exposed persons. Laboratory research showed that vibrotactile thresholds should be expected to depend upon vibration exposure immediately prior to the test. The vibration frequency and general configuration of the vibrotactile apparatus also influenced threshold. An awareness of these factors allows guidelines for their control to be suggested.